Eight induced pluripotent stem cell lines (iPSCs) derived from two patients with Leukocyte adhesion deficiency Type I (LAD I) with mutations in the ITGB2 gene - Julia Fekadu-Siebald; Nina V Fuchs; Stella Zahn; Marcel G E Rommel; Franziska Schenk; Sabine Huenecke; Melanie Bremm; Hermann Kreyenberg; Zyrafete Kuci; Eva-Maria Jacobsen; Manfred Hoenig; Klaus Schwarz; et al. (Stem Cell Research)
Leukocyte Adhesion Deficiency Type I (LAD I) is a rare inborn error of immunity caused by mutations in the ITGB2 gene coding for β2-integrin CD18 on the surface of leukocytes. Affected patients display severe clinical manifestations with life threatening infections and inflammatory complications due to an impaired ability of leukocytes to transmigrate from the blood vessel to the tissue. Here we describe the generation of eight induced pluripotent stem cell lines from two patients with LAD I and mutations in the ITGB2 gene. With this project we contribute patient individualized cell lines for explorative research in a rare disease.